Introducción a la Tecnología de Injertos a la Industria de Tomate en la Florida: Beneficios Potenciales y Retos - Monica Ozores-Hampton; Xin Zhao; Miriam Ortez (EDIS)
HS1187, a 7-page illustrated fact sheet by Monica Ozores-Hampton, Xin Zhao, and Miriam Ortez, describes benefits and risks of using grafting technology in tomato production. Includes references. Published by the UF Department of Horticultural Sciences, December 2010.